Interleukin-10 Has Different Effects on Proliferation of Listeria monocytogenes in Livers and Spleens of Mice - Samsom, Janneke N. (American Society for Microbiology, 2000)
The aim of this study was to investigate the effect of interleukin-10 (IL-10) on the course of Listeria monocytogenes infection in naive and immune mice. Treatment with IL-10 during the course of a primary infection significantly decreased the number of bacteria in the spleen and did not affect the number in the liver. During a secondary infection in immune mice treated with IL-10, the number of bacteria was significantly lower in the spleen but significantly higher in the liver in comparison to mock-treated immune mice. IL-10 treatment during a primary Listeria infection decreased the concentration of gamma interferon (IFN-γ) in plasma and the toxoplasmastatic activity of macrophages, whereas it increased the percentage of mildly CD3-positive T cells in the spleen. During a secondary infection, the concentration of IFN-γ in plasma was decreased on day 1 but remained unaffected during later days of infection. From these results, we conclude that IL-10 has different effects on the proliferation of L. monocytogenes in the spleen and liver during primary and secondary Listeria infections.